2020
DOI: 10.1038/s41598-020-72663-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between domains of physical activity and cardiac autonomic modulation in adults: a cross-sectional study

Abstract: This study aimed to analyze the relationship of physical activity in different domains with cardiac autonomic modulation in adults. A sample of 252 adults was randomly selected, with mean age of 42.1 (± 16.5) years, being 58% of women. Cardiac autonomic modulation was assessed through indexes of heart rate variability in time (SDNN, RMSSD) and frequency (LF, HF) domains for linear method, and by Poincaré plot for non-linear method (SD1, SD2 components). Domains of PA (occupation, sport, leisure time/commuting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…TA B L E 4 Bivariate correlations between the vagus nerve' cross-sectional area (VN CSA) and parameters of heart rate variability probands [35]. Thus, future studies should also assess the physical activity before the time point of diagnosis as a potential confounder when examining the autonomic nervous system in ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 4 Bivariate correlations between the vagus nerve' cross-sectional area (VN CSA) and parameters of heart rate variability probands [35]. Thus, future studies should also assess the physical activity before the time point of diagnosis as a potential confounder when examining the autonomic nervous system in ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“… 3 In contrast, engaging in physical activity (PA) is an important lifestyle habit that has been positively associated with high CAM, because PA improves vagal activity. 4 Nonetheless, it is not clear in the literature whether different intensities of PA could eliminate or at least mitigate the relationship between smoking and reduced CAM. Our hypothesis was that very vigorous PA would mitigate the effects of smoking on CAM.…”
Section: To the Editormentioning
confidence: 99%
“…The reason for similar cardiac parasympathetic hypoactivity in moderate and severe FM is unknown. Indeed, a physically inactive lifestyle is associated with impaired cardiovascular autonomic modulation in healthy individuals ( Hughson and Shoemaker, 2015 ; Zaffalon-Júnior et al, 2018 ), particularly for parasympathetic tone ( Buchheit et al, 2005 ; Niemela et al, 2019 ; Tebar et al, 2020 ). However, the RMSSD for moderate and severe FM in this study (~21 ms in average) was close to that reported in other studies with middle-aged FM women (~19 to 21 ms in average) ( Kang et al, 2016 ; Kulshreshtha et al, 2012 ; Rost et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the dysautonomia seems to be directly related to FM pathogenesis ( Lerma et al, 2011 ; Martinez-Lavin, 2007 ; Schamne et al, 2021 ), the sedentary lifestyle of FM patients promotes a physical deconditioning, which aggravates the dysautonomia ( Kulshreshtha and Deepak, 2013 ; Meeus et al, 2013 ). It is noteworthy that reduced physical activity and increased bouts of sedentary time are negatively associated with resting cardiac parasympathetic tone ( Buchheit et al, 2005 ; Niemela et al, 2019 ; Tebar et al, 2020 ). Interestingly, as the FM severity increases the level of physical activity reduces ( Segura-Jiménez et al, 2015 ; Segura-Jiménez et al, 2020 ), consequently reducing multiple components of physical fitness ( Aparicio et al, 2013 ; Góes et al, 2012 ; Soriano-Maldonado et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%